2013
DOI: 10.3892/etm.2013.915
|View full text |Cite
|
Sign up to set email alerts
|

miR-342 is associated with estrogen receptor-α expression and response to tamoxifen in breast cancer

Abstract: Estrogen receptor-α (ERα) is essential for estrogen-dependent growth and its level of expression is a crucial determinant of response to endocrine therapy and prognosis in ERα-positive breast cancer. Breast cancer patients show a wide range of ERα expression levels which change in individual patients during disease progression and in response to systemic therapies. However, little is known concerning how the expression of ERα is regulated in human breast cancer. Recently, several microRNAs (miRNAs) have been i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 19 publications
5
54
0
Order By: Relevance
“…Importantly, overexpression of miR-342 has been shown to inhibit cell proliferation and invasion in cervical and colorectal cancer [17,18]. Diagnostic and prognostic values of miR-342 expression have additionally been highlighted in acute myeloid leukemia, breast cancer, and colon cancer [27][28][29]. In the current study, we established a role of miR-342-3p as an effective NSCLC suppressor.…”
Section: Discussionsupporting
confidence: 53%
“…Importantly, overexpression of miR-342 has been shown to inhibit cell proliferation and invasion in cervical and colorectal cancer [17,18]. Diagnostic and prognostic values of miR-342 expression have additionally been highlighted in acute myeloid leukemia, breast cancer, and colon cancer [27][28][29]. In the current study, we established a role of miR-342-3p as an effective NSCLC suppressor.…”
Section: Discussionsupporting
confidence: 53%
“…miR-342 expression has been beforehand described as significantly higher in ER þ samples, and was included in a predictor of ER status together with miR-135b and miR-190 (33). Moreover, miR-342 expression was positively correlated with ERa mRNA expression in human breast cancer (34). miR-205 was significantly underexpressed in triple-negative primary breast cancers when compared with tumor-associated normal samples.…”
Section: Mirna Expression Analysismentioning
confidence: 82%
“…The loss of metadherin has been shown to restore sensitivity to endocrine therapy and is correlated with disease-free survival in ER-positive patients. 58 He et al 36 demonstrated that miR-342 expression was positively correlated with ER expression and also found that the introduction of miR-342 into estrogendependent breast cancer cell lines enhanced their sensitivity to tamoxifen-induced apoptosis. In agreement with this, Cittelly et al 59 reported that the downregulation of miR-342 expression was associated with tamoxifen resistance.…”
Section: Mirna In Hormone Receptor-positive/her2-negative Breast Cancermentioning
confidence: 98%
“…34 MiR-342 influences the ER expression level and the response to tamoxifen. 35,36 MiR-10b, miR-26a and miR-153 have been suggested to be potential biomarkers of triple-negative breast cancer (TNBC). 37 miRNAs associated with each subtype of breast cancer are shown in Table 3.…”
Section: Mirna and Intrinsic Subtypes Of Breast Cancermentioning
confidence: 99%